Ductilizing Ti19Zr19Hf19Nb19TM5Be19 (TM = Fe, Co, Ni and Cu) high-entropy bulk metallic glass composites via in-situ precipitated refractory high-entropy alloy dendrites. (January 2023) - Liu, M.L.; Li, W.; Zeng, S.; Li, Y.F.; Fu, H.M.; Li, H.; Wang, A.M.; Lin, X.P.; Zhang, H.F.; Zhu, Z.W.
Abstract: In this work, a series of Ti19 Zr19 Hf19 Nb19 TM5 Be19 (at.%, TM = Fe, Co, Ni and Cu) high-entropy bulk metallic glass composites (HE-BMGCs) were successfully developed to address the absence of tensile ductility in high-entropy bulk metallic glasses (HE-BMGs). It is shown that the mechanical properties of HE-BMGCs are jointly affected by the two constituent phases of refractory high-entropy alloy (RHEA) dendrites and HE-BMG matrix. The present composites show that the good tensile ductility as well as excellent work-hardening capability at ambient temperature. Based on the post-deformation microstructure and theoretical analyses, cross slips dominate the deformation mechanism of HE-BMGCs, and it is found that the dislocation multiplication mechanism composed of dislocation pinning and double cross-slip is very prevalent in current composites. Therein, the dislocation multiplication of RHEA dendrites facilitates the inhibition and retardation to the propagation of shear bands in the HE-BMG matrix, which is responsible for the good tensile ductility of HE-BMGCs. Additionally, the excellent work-hardening capability of composites is attribute to severe dislocation interactions caused by intrinsic local-regional multicomponent fluctuations and dislocation cross-slips in RHEA dendrites. Our research results not only aid in understanding the underlying deformation mechanism of HE-BMGCs, but also offer a novel perspective for designing the ductile high-entropy dual-phase alloys. Highlights: Cross slips dominate the deformation mechanism of a series of Ti19 Zr19 Hf19 Nb19 TM5 Be19 (at.%, TM = Fe, Co, Ni and Cu) HE-BMGCs. Dislocation multiplication composed of dislocation pinning and double cross-slip is prevalent in all HE-BMGCs. The inhibition of RHEA dendrites on SBs propagation is the reason why HE-BMGCs has good tensile ductility.